Pengetahuan Ibu tentang Posyandu dengan Cakupan Kunjungan (D/S) Balita - Anisa Supriyanti; Widy Nurwiandani; Diah Yuliantina (Sekolah Tinggi Ilmu Kesehatan AKBIDYO, 2021)
Background : Based on the Republic of Indonesia Ministry of Health in 2013 the coverage (D / S) of toddlers in Indonesia amounted to 80.30%, in the Special Region of Yogyakarta in 2014 reached 79.1% had not met the Ministry of Health Renstra target, the level of community participation in Bantul Regency in weighing Posyandu (D / S) of 79.02% and still below 80%, the number of under-five deaths in Bantul Regency in 2014 was 131 toddlers, the highest number of under-five mortality among the five regencies in DIY, for D/S coverage which was still low in Bantul Regency below 80% namely Bantul 1 Health Center is 75.47%, in the Bantul I Health Center area the scope of weighing (D/S) is still low, namely in Trirenggo Village the D / S coverage in October 2015 was 75.95%. Objective: To find out the relationship between the knowledge of mothers about posyandu and the coverage of visits (D / S) of toddlers at Posyandu Mekarsari, Trirenggo, Bantul, Yogyakarta.Method: This study was conducted at Mekarsari Trirenggo Bantul Posyandu in February, the study design used Bivariate Correlation with a cross sectional approach. The population of mothers who have children aged 12-60 months who live in the Mekarsari Posyandu area is 65 respondents. The sampling technique by means of total sampling. Analysis using Chi Square.Results: By using the Chi Square formula, the value of X2 calculated is equal to6,644 with an error rate of 5% (X2 count> X2 table) and p-value <0.05. Respondents in this study can be categorized as having less knowledge, namely 32 respondents (49.2%) and not active in conducting Posyandu visits 34 respondents (52.3%).Conclusion: There is a relationship between knowledge of mothers about Posyandu and coverage of visits (D / S) of children under five at Posyandu Mekarsari Trirenggo Bantul.Keywords: Knowledge about Posyandu, coverage of visits (D/S) toddlers